Characterization of Nanocomposite Casein-Chitosan with Addition TiO2 Toward Physical Stability, Emulsifying Activity Index, and Microstructure (Jurnal Ilmu dan Teknologi Hasil Ternak, 2021)
The purpose of this research was to determine the characteristic of physical properties and emulsifying activity index with different concentrations (0%, 1%, 3%, and 5% (v/v)) on the viscosity, solubility, turbidity, emulsifying activity index, and microstructure. The experiment was designed by Completely Randomized Design (CRD). The data were analyzed by Analysis of Variance (ANOVA) and continued by the Least Significant Difference (LSD) test. The addition of TiO2 with different concentrations gave a highly significant difference characteristic on syneresis, viscosity, solubility, turbidity, and emulsifying activity index (P<0.01) and the addition of TiO2 with different concentrations show the different effect on protein casein and chitosan aggregate. The surface microstructure of nanocomposite casein-chitosan addition of TiO2 for low-level concentration TiO2. It can be presumed presence of TiO2 as a photocatalyst indicated increasing the syneresis, viscosity, solubility, turbidity, and emulsifying activity index.